The Tabuik Tradition in the Formation of Islamic Values in Pariaman - Muhamad Syahreza; Muhammad Akmansyah; Umi Hijriyah (Cultura Islamica: Journal of Islamic Studies, Management, and Culture, 2025)
One of the annual events held in Pariaman City is the Tabuik Tradition. This tradition is organized based on Islamic principles to honor the death of Hussein, the grandson of Prophet Muhammad SAW. The celebration actually falls on the tenth of Muharram in the Hijri calendar. This study employs a descriptive methodology with a qualitative approach. To thoroughly understand how the Tabuik tradition shapes Islamic ideals in Pariaman, a qualitative method is chosen. The embedding of Islamic values within the Tabuik tradition, the function of the Tabuik tradition as a religious practice in Islam, and the role of the Tabuik tradition in building Islamic values in Pariaman are specific phenomena that are central to this approach. Interviews, observations, and documentation were used as the primary data collection methods. This approach enables scholars to examine the unique context of the Tabuik tradition in shaping Islamic ideals in Pariaman and to present a comprehensive picture of the actual situation on the ground. The results of the study indicate that the Tabuik Tradition in Pariaman is a complex amalgamation of social support, religious principles, and cultural identity. Through this tradition, the people of Pariaman strengthen their Islamic practices in response to contemporary dynamics, understand historical heritage, and express solidarity. The shared concern of both the government and the community for the preservation of the Tabuik Tradition reflects a collective desire to safeguard and nurture this rich cultural heritage so it can be passed on to future generations.